O-13 The CARiAD study. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Poolman, Marlise; Roberts, Jessica; Hiscock, Julia; Hendry, Annie; Wright, Stella; Wilkinson, Clare
Abstract : CARer-ADministration of as-needed sub-cutaneous medication for breakthrough symptoms in homebased dying patients: a UK study (CARiAD) Background: While the majority of seriously ill people wish to die at home, only half achieve this. The likelihood of someone dying at home often depends on the availability of able and willing lay carers to support them. Whilst this often involves giving medication, people in the last days of life may be unable to take oral medication. Regular medications can be administered using a syringe driver. When top-up medication is required for breakthrough symptoms, a clinician must travel to the home to administer as-needed subcutaneous medication. Aims: To determine if carer-administration of as-needed subcutaneous medication for four frequent breakthrough symptoms (pain, nausea, restlessness and noisy breathing) in home-based dying patients is feasible and acceptable in the UK. Methods: Adult patients anticipated to be in the last weeks of life who were likely to lose the oral route and expressed a preference to die at home were recruited with their carers to an external randomised pilot trial across three UK sites (North Wales, South Wales and Gloucestershire). Patient/Carer dyads randomised to the intervention arm received a manualised training package delivered by their community nursing teams. Dyads in the control arm received usual care. Carers in both arms completed carer diaries and outcome measures. Results: Forty dyads were recruited. The main outcomes of interest are feasibility, acceptability, recruitment rates, attrition and selection of the most appropriate outcomes measures. Conclusions: Findings will inform a definitive Phase III randomised controlled trial. This study is funded by the National Institute for Health Research (NIHR) HTA (Grant Reference Number 15/10/37). The views expressed are those of the authors and not necessarily those of the NIHR or the Department of Health and Social Care.